Perovskite structure associated with precious metals: Influence on heterogenous catalytic process - Teixeira, Guilhermina Ferreira; Silva Junior, Euripedes [UNESP]; Vilela, Ramon; Zaghete, Maria Aparecida [UNESP]; Colmati, Flávio (MDPI, 2019)
The use of perovskite-based materials and their derivatives can have an important role in the heterogeneous catalytic field based on photochemical processes. Photochemical reactions have a great potential to solve environmental damage issues. The presence of precious metals in the perovskite structure (i.e., Ag, Au, or Pt) may improve its efficiency significantly. The precious metal may comprise the perovskite lattice as well as form a heterostructure with it. The efficiency of catalytic materials is directly related to processing conditions. Based on this, this review will address the use of perovskite materials combined with precious metal as well as their processing methods for the use in catalyzed reactions.
Keywords: Perovskite; Photochemical; Photodegradation; Precious metals